2013
DOI: 10.1117/12.1000152
|View full text |Cite
|
Sign up to set email alerts
|

Brain and muscle oxygenation monitoring using near-infrared spectroscopy (NIRS) during all-night sleep

Abstract: The hemodynamic changes during natural human sleep are still not well understood. NIRS is ideally suited for monitoring the hemodynamic changes during sleep due to the properties of local measurement, totally safe application and good tolerance to motion. Several studies have been conducted using NIRS in both normal subjects and patients with various sleep disorders during sleep to characterize the hemodynamic changing patterns during different sleep stages and during different symptoms such as obstructive apn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Deoxygenated hemoglobin levels display a reverse trend resulting in no net change in total hemoglobin levels. According to a study that measured hemoglobin levels both in muscle and cortex during sleep, HbO level decreases and HbR level increases during onset of sleep but this trend is reversed during transition to deep sleep (SWS) (Zhang and Khatami, 2013). As the researchers observed this transition both in brain and muscle tissue, they concluded that it is a systemic physiological response rather than having cortical specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxygenated hemoglobin levels display a reverse trend resulting in no net change in total hemoglobin levels. According to a study that measured hemoglobin levels both in muscle and cortex during sleep, HbO level decreases and HbR level increases during onset of sleep but this trend is reversed during transition to deep sleep (SWS) (Zhang and Khatami, 2013). As the researchers observed this transition both in brain and muscle tissue, they concluded that it is a systemic physiological response rather than having cortical specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Several well-established neuroimaging methodologies including computed tomography (CT), functional magnetic resonance imaging (fMRI), positron emission tomography (PET), single-photon emission computed tomography (SPECT), transcranial Doppler (TCD), and near-infrared spectroscopy (NIRS) have been widely used to study cerebral autoregulation mechanism under various physiological and pathological states in both healthy subjects and patients. [12][13][14][15][16][17][18][19] Several attempts to determine cerebral hemodynamics in OSA using these techniques faced some limitations. CT, fMRI, PET and SPECT are only suitable to study the cerebral hemodynamics in OSA patients during wakefulness, [20][21][22] but not during all night sleep due to obvious reasons including safety issues, radiation, high magnetic¯elds, loud noises, motion artifacts, compatibility of CPAP device, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these techniques, as a totally non-invasive and non-radiation optical method NIRS can robustly measure oxygenated (HbO2) and deoxygenated (HHb) hemoglobin (Hb), blood flow (BF), blood volume (BV) and tissue oxygen saturation index (TOI) changes in local cerebral regions [10][11] . It is a powerful tool to study cerebral hemodynamics during all night sleep 12 . Several studies with NIRS repeatedly reported an impairment of cerebral oxygenation in the patients with sleep apnea [13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%